Fuzzy Adaptive PID Control of a New Hydraulic Erecting Mechanism - Liang Li; Jian Xie; Wei Li (Universitas Ahmad Dahlan, 2013)
Conventional erecting mechanism is cumbersome and the erecting velocity is slow, so a new hydraulic erecting mechanism is introduced in this paper. But it has two problems. First is the cooperation problem between the erect cylinder and the horizontal cylinder. Second, the nonlinearities and uncertainties exist in the system make the control precision poor. So the combined simulation model is built based on the software AMESim and Simulink. And from this model, the best cooperation time is confirmed. Further, the fuzzy adaptive PID controller is introduced to improve the control performance aiming to the nonlinearities and uncertainties. The fuzzy inference rules and parameters of the controller are also presented in this paper. Experiment results show that the cooperation time which received from the simulation is correct, and the fuzzy adaptive PID controller has nice tracking performance compared to the conventional PID controller and fuzzy controller.